Time-course transcriptome analysis reveals regulation of Arabidopsis seed dormancy by the transcription factors WOX11/12. (19th November 2022) - Liao, Jiakai; Deng, Ban; Cai, Xinyu; Yang, Qixin; Hu, Bangping; Cong, Jiajing; Zhang, Yuxiang; Wang, Gang; Xin, Guiliang; Li, Yuting; Yang, Li; Zhang, Daizhen; et al.
Abstract: The induction of seed dormancy and its release involve a finely regulated genetic program controlled by various environmental and developmental cues that are critical for plant survival and population expansion. Light plays a key role in seed dormancy and germination, but the molecular mechanisms underlying the control of dormancy are unclear. In the present study, high-resolution temporal RNA-seq in Arabidopsis identified WOX11 as encoding a hub transcription factor during the seed dormancy induction and release stages. This gene might have evolved from gymnosperms and expanded in angiosperms with highly conserved expression patterns in seeds. WOX11 and its homolog WOX12 were highly expressed from 2 d after pollination, and mRNA abundance was greatly increased during the seed dormancy induction and release stages. Further, we found that WOX11 plays a role in the regulation of seed dormancy downstream of phytochrome B (PHYB)-mediated red-light signaling during the induction stage, indicating that WOX11/12 are newly identified components of red-light signaling transduction. Taken together, our results suggest that WOX11/12-mediated PHYB signaling regulates seed dormancy in Arabidopsis, and provide insights into the developmental regulation and evolutionary adaptation of plants to changes in the light environment. Abstract : WOX11/WOX12 are activated by phytocrome B-mediated red-light signaling during the seed maturation stage, and play roles in regulating seed dormancy by modulating gibberellin signaling.